Conditional Loss of BAF (mSWI/SNF) Scaffolding Subunits Affects Specification and Proliferation of Oligodendrocyte Precursors in Developing Mouse Forebrain - Abbas, Eman; Hassan, Mohamed A.; Sokpor, Godwin; Kiszka, Kamila; Pham, Linh; Kerimoglu, Cemil; Fischer, Andre; Nguyen, Huu Phuc; Staiger, Jochen F.; Tuoc, Tran (Frontiers in Cell and Developmental Biology, 2021)
Oligodendrocytes are responsible for axon myelination in the brain and spinal cord. Generation of oligodendrocytes entails highly regulated multistage neurodevelopmental events, including proliferation, differentiation and maturation. The chromatin remodeling BAF (mSWI/SNF) complex is a notable regulator of neural development. In our previous studies, we determined the indispensability of the BAF complex scaffolding subunits BAF155 and BAF170 for neurogenesis, whereas their role in gliogenesis is unknown. Here, we show that the expression of BAF155 and BAF170 is essential for the genesis of oligodendrocytes during brain development. We report that the ablation of BAF155 and BAF170 in the dorsal telencephalic (dTel) neural progenitors or in oligodendrocyte-producing progenitors in the ventral telencephalon (vTel) in double-conditional knockout (dcKO) mouse mutants, perturbed the process of oligodendrogenesis. Molecular marker and cell cycle analyses revealed impairment of oligodendrocyte precursor specification and proliferation, as well as overt depletion of oligodendrocytes pool in dcKO mutants. Our findings unveil a central role of BAF155 and BAF170 in oligodendrogenesis, and thus substantiate the involvement of the BAF complex in the production of oligodendrocytes in the forebrain.